PENGARUH FINANCIAL LITERACY DAN FINANCIAL SELF EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA USAHA KECIL MENENGAH DI KOTA TIMIKA - Narew, Ignasius; Rosdiana, Rosdiana; Pondaag, Elfira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Small and Medium Enterprises (SMEs) play a crucial role in driving economic growth, including in Timika, Papua. However, business sustainability is often constrained by weak financial management practices. This study aims to analyze the influence of financial literacy and financial self-efficacy on the financial management behavior of SME actors in Timika. A quantitative research method with an explanatory approach was employed. Data were collected through a Likert-scale questionnaire administered to 100 respondents selected using purposive sampling. The data were analyzed using multiple linear regression. The findings reveal that both financial literacy and financial self-efficacy have a positive and significant effect on financial management behavior. Financial literacy contributes the most significant influence, particularly in aspects of budgeting, savings, loans, protection, and investment. Meanwhile, financial self-efficacy also enhances financial behavior through individuals’ confidence in facing challenges and making financial decisions. Together, these two variables explain 77.9% of the variance in SMEs’ financial management behavior in Timika. The results highlight the importance of strengthening financial literacy and enhancing financial self-efficacy through training, education, and business mentoring to enable SMEs to manage their finances effectively, sustainably, and competitively.